Experimental study on mechanical properties of S-RM with different rock block proportions in fault zone - Peng-fei Wang; Xue-yang Xing; Yong-cheng Jin; Jian-biao Bai; Chang-hong Li (Scientific Reports)
Abstract The distribution range of soil-rock mixtures (S-RM) in fault zones is wide, with significant differences in mechanical properties, making them the main sites for rock instability and support structure failure in mines. This paper takes the Sanshan Island fault zone as the engineering background, and uses a self-designed small-scale test device to conduct triaxial compression tests to study the strength and deformation failure laws of S-RMs with different rock block proportions (20%, 40%, 60%, and 80%). Combined with numerical simulation test results, the spatial transport laws and microscopic deformation failure characteristics of particles with different particle sizes in the S-RM are revealed. The main conclusions drawn are as follows: (1) For S-RMs with rock block proportions (RBP) of 20%, 40%, and 60%, there is a linear positive correlation between confining pressure and peak strength. When the RBP increases to 80%, there is a non-linear positive correlation between the confining pressure and peak strength of the S-RM sample. Under the same increase in confining pressure, the increase in peak strength of the sample decreases. The influence of confining pressure on the strength and deformation characteristics of S-RMs with high RBP is reduced. (2) During the process of increasing the RBP from 20 to 60%, there is a linear positive correlation between the RBP and peak strength of the S-RM sample. When the RBP increases to 80%, the peak strength of the sample experiences a sudden increase, with an increase of nearly 80 kPa in peak strength. When the RBP is high, the S-RM sample exhibits the mechanical properties of block rocks. (3) The cohesion and internal friction angle of the S-RM sample are positively correlated with the RBP. During the process of increasing the RBP from 20 to 80%, the cohesion increases from 83.12 kPa to 119.38 kPa, and the friction angle increases from 6° to 11°. (4) When the RBP is low (20% and 40%), as the experiment progresses, a significant conjugate shear deformation zone will form within the S-RM sample, and block rock particles will migrate towards this area and undergo shear slip failure between particles. When the RBP is high (60% and 80%), splitting failure mainly occurs at the bonding surface between block rock particles and soil particles inside the sample, and the contact force between particles is relatively large. The relevant research results have important social and economic value for revealing the fracture failure laws of rock masses in fault zones and ensuring the safe development of human engineering activities.